2022
DOI: 10.1021/acsaem.2c00472
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Property Relationship of Oxygen-Doped Two-Dimensional Gallium Selenide for Hydrogen Evolution Reaction Revealed from Density Functional Theory

Abstract: Two-dimensional (2D) gallium selenide (GaSe) is known for its inert surface and wide bandgap, limiting its application as a photocatalytic material for the hydrogen evolution reaction (HER). Partial substitution of Se with O atoms can improve its catalytic efficiency. This work discovered that the surface activity of the substitutional O-doped single-layer GaSe surfaces (GaSe1–x O x , for x ≤ 22%) and their bandgap sizes are dependent on the detailed atomic configuration of the dopants, as revealed from densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 65 publications
(122 reference statements)
3
16
0
Order By: Relevance
“…The changes in the band state of gallium oxyselenide may be attributed to the potential development of a novel unoccupied band introduced by the oxygen atom, positioned between the conduction band maximum (CBM) and the original VBM of pure GaSe. Additionally, the Ga–O band exhibits a shorter length (2.1 Å) compared to the Ga–Se band (2.6 Å), resulting in tensile strains within the plane and compressive strains perpendicular to it. Previous studies have suggested that both tensile and compressive strains could decrease the band gap. The flat band potentials of GaSe, GaSe 0.40 O 0.60 , GaSe 0.31 O 0.69 , and GaSe 0.19 O 0.81 were determined as 0.30, 0.32, 0.39, and 0.61 eV, respectively, from the Mott–Schottky plots depicted in Figure S6, which increased with improved annealing temperature, as demonstrated in Figure c.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in the band state of gallium oxyselenide may be attributed to the potential development of a novel unoccupied band introduced by the oxygen atom, positioned between the conduction band maximum (CBM) and the original VBM of pure GaSe. Additionally, the Ga–O band exhibits a shorter length (2.1 Å) compared to the Ga–Se band (2.6 Å), resulting in tensile strains within the plane and compressive strains perpendicular to it. Previous studies have suggested that both tensile and compressive strains could decrease the band gap. The flat band potentials of GaSe, GaSe 0.40 O 0.60 , GaSe 0.31 O 0.69 , and GaSe 0.19 O 0.81 were determined as 0.30, 0.32, 0.39, and 0.61 eV, respectively, from the Mott–Schottky plots depicted in Figure S6, which increased with improved annealing temperature, as demonstrated in Figure c.…”
Section: Results and Discussionmentioning
confidence: 99%
“…positioned between the conduction band maximum (CBM) and the original VBM of pure GaSe. Additionally, the Ga−O band exhibits a shorter length (2.1 Å) compared to the Ga−Se band (2.6 Å),60 resulting in tensile strains within the plane and compressive strains perpendicular to it. Previous studies have suggested that both tensile and compressive strains could decrease the band gap.61−63 The flat band potentials of GaSe,…”
mentioning
confidence: 99%
“…In our previous work, not only the concentration but also the atomic configuration of O-dopants were identified as essential factors for tuning the surface catalytic activity of GaSe 1−x O x for HER; interestingly, the presence of localized dopant arrangements would play an essential role in enhancing its catalytic activity. 42 To be discussed below, the atomic configuration of the Odopants is also an important factor to improve the catalytic efficiency for the OER, as predicted with our GaSe supercell with O atoms. In this study, GaSe 1−x O x with up to 22% O content was investigated.…”
Section: Effects Of Concentration and Atomic Configuration Of Dopants...mentioning
confidence: 93%
“…42 Oxygen doping can also significantly alter the electronic structure of GaSe by reducing its wide bandgap while still keeping the positions of conduction band minimum (CBM) and valence band maximum (VBM) suitable for photochemical water splitting reactions. 42 In this work, the surface activity and catalytic performance of oxygen-doped GaSe (GaSe 1−x O x ; x = 6, 11, 17, and 22%) toward the OER are also theoretically studied. The primary objective is to predict how the performance of OER may be influenced by different concentrations and atomic configurations of the dopants on the O-doped GaSe surfaces, which have been suggested to have significant effects on the complementary HER process.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation